Frequencies of Genetic Polymorphisms of Clinically Relevant Gene-Drug Pairs in a German Psychiatric Inpatient Population - Hahn, Martina; Müller, Daniel J.; Roll, Sibylle C. (Pharmacopsychiatry, 2020)
Introduction Genetic variation is known to affect enzymatic activities allowing differentiating various metabolizer types (e. g., slow or rapid metabolizers), in particular CYP2C19 and CYP2D6.Methods PGx-testing was conducted in adult major depressive disorder inpatients admitted to the Vitos Klinik Eichberg between 11/2016 and 7/2017 (n=108, 57% female). We conducted a two-sided Z-Test (p=0.05) to analyze and compare frequencies of CYP2D6, CYP2C19, CYP3A4, CYP3A5 and CYP2C9 metabolizer groups with other European and psychiatric inpatient cohorts. The HLA-A and –B genes were also analyzed.Results Non-normal metabolizer status of CYP2D6 were present in 47%. More specifically, 35 % were intermediate, 7% poor and 4% ultra-rapid metabolizers. 68% were CYP2C19 non-normal metabolizers. 8% were ultra-rapid and 31% rapid metabolizers. Notably, only 13% were NM for CYP2C19 and NM for CYP2D6 (activity score of 1 or more). For CYP2C9 we found 16% to be intermediate metabolizers, 1.0% poor metabolizer. CYP3A4 and CYP3A5 genetic polymorphisms were present in 25% and 19% respectively. HLA-B TAG- SNPs for *15:01 was positive in 25 patients, showing the need for different Tag-SNPs in Caucasians. HLA-B *57:01 TAG-SNP was positive in 8% of the patients, HLA-A TAG-SNP for *31:01 in Caucasians was positive in 9%. Z-Test showed statistical significance for our results.Discussion Our results suggest that our psychiatric inpatients were enriched with genotypes consistent with non-normal drug metabolism compared to reference populations. We therefore conclude that pharmacogenetic testing should be implemented in clinical practice to guide drug therapy.
Keywords: Cytochrome P450 (CYP) enzymes; Pharmacogenetics; psychiatry; Antidepressants; personalized medicine